An Overview on Online Education (International Journal of Innovative Research in Computer Science & Technology, 2020)
As blended and online learning grow less  common education, instructors must rethink fundamental  issues such as educating, learning, and assessment in  unconventional settings. Such concerns include knowing  how formative assessment works for online and blended  learning, as well as the reliability and validity of evaluation  in digital environments in regard to achieving the intended  purposes. The purpose of this article is to provide a  systematic qualitative review of the research literature on  online formative assessment for higher education. One  method used in this review was an integrative story review  that includes methodical searching, reading, then writing  of the literature to draw up major themes and findings of  work in this topic. The authors used qualitative research  criteria for choosing and examine the existing literature,  focusing on examining and defining the core themes that  are central to the concept of formative assessment, with a  special emphasis on its implementation in online and  blended settings. For summative assessment, students,  peers, and instructors employed a range of tactics, many of  which were connected to digital sites such as self-test  quizzes, conversation forums, and e-portfolios. The  advantages claimed include increased student participation  and centrality within the process as important participants,  as well as the formation of a learning society[1].
Keywords: Computer; Exam; Education; Online Assessment